2019
DOI: 10.1002/pmrj.12268
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Dextrose Prolotherapy for Rotator Cuff Tendinopathy: A Systematic Review

Abstract: Objective To systematically review and evaluate the efficacy and complication profile of prolotherapy using hyperosmolar dextrose solution injection for rotator cuff tendinopathy. Literature Survey MEDLINE, EMBASE, CINAHL, and the Cochrane Central Register of Controlled Trials (from inception to 1 July, 2019). Methodology A comprehensive search was completed to identify randomized controlled trials addressing prolotherapy using hyperosmolar dextrose solution for rotator cuff tendinopathy. Two reviewers indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…showed that injection of dextrose prolotherapy for the supraspinatus tendon can reduce pain and improve functional outcome over a 6-month period. There was no adverse effects on tendon structure and, in fact, prolotherapy groups showed significant improvements in ultrasound characteristics of the supraspinatus tendon, decreasing pain, with increased range of motion and strength of muscle [32].…”
Section: Discussionmentioning
confidence: 84%
“…showed that injection of dextrose prolotherapy for the supraspinatus tendon can reduce pain and improve functional outcome over a 6-month period. There was no adverse effects on tendon structure and, in fact, prolotherapy groups showed significant improvements in ultrasound characteristics of the supraspinatus tendon, decreasing pain, with increased range of motion and strength of muscle [32].…”
Section: Discussionmentioning
confidence: 84%
“…In recent years, prolotherapy has been widely used and proposed as an alternative treatment to steroid injection. 4 Studies have compared the effects of prolotherapy with those of steroid. 7 Nasiri et al 23 reported that in terms of VAS and SPADI scores, prolotherapy was not inferior to corticosteroid injection in patients with rotator cuff–related shoulder pain, with the effect lasting up to 12 weeks after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 3 In recent years, prolotherapy has been considered an alternative treatment for patients with chronic rotator cuff tendinopathy. 4 Prolotherapy is an injection-based therapy that exerts a regenerative effect on patients with chronic musculoskeletal pain. 25 Hypertonic dextrose is one of the most commonly used prolotherapy agents and is considered to induce cell proliferation, thus strengthening and healing the tendon.…”
mentioning
confidence: 99%
“…Non-adverse events were not reported with dextrose prolotherapy in this case as in many preceding cases. [23] CONCLUSION RC tears present with severe shoulder pain, weakness of shoulder flexion, abduction or external rotation, that can significantly impact activities of daily life. Prolotherapy is the injection of growth factors or growth factor production stimulants to promote regeneration of normal cells and tissue.…”
Section: Discussionmentioning
confidence: 99%